Drug‐Induced Liver Injury by Selective Androgenic Receptor Modulators. Issue 3 (3rd January 2020) - Flores, Joan Ericka; Chitturi, Shivakumar; Walker, Sarah
Abstract : Selective androgenic receptor modulators (SARMs) have not been approved by the U.S. Food and Drug Administration but they are heavily promoted as alternatives to androgenic anabolic steroids. We present two cases of liver injury associated with SARMs.